2021
DOI: 10.1038/s41598-021-94910-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of the classification and severity of heart failure with the incidence of contrast-induced acute kidney injury

Abstract: Congestive heart failure (HF) is a known risk factor of contrast-induced acute kidney injury (CI-AKI). However, the relationship of the classification and severity of HF with CI-AKI remains under-explored. From January 2009 to April 2019, we recruited patients undergoing elective PCI who had complete pre- and post-operative creatinine data. According to the levels of ejection fraction (EF), HF was classified as HF with reduced EF (HFrEF) [EF < 40%], HF with mid-range EF (HFmrEF) [EF 40–49%] and HF with pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Anemia Systematic review and meta-analysis Wei et al (191) Hypotension Systematic review and meta-analysis Ong et al (192) Volume Depletion and Hemodynamic Instability Systematic review and meta-analysis Tea et al (193) NSAID, diuretics and other nephrotoxic drugs Systematic review and meta-analysis Zhang et al (194) ACE-I/ARB usage Randomized trial parallel-group, single-center CAPTAIN trial (195) Acute heart failure NYHA III-IV Multicenter retrospective study Tian et al (196) Hypoalbuminemia Systematic review and meta-analysis Liwei et al (197) Peri-procedural hyperglycemia Systematic review and meta-analysis Jakrin et al (198) Patient…”
Section: Patient-related Risk Factors-modifiable Weight Of Evidence E...mentioning
confidence: 99%
“…Anemia Systematic review and meta-analysis Wei et al (191) Hypotension Systematic review and meta-analysis Ong et al (192) Volume Depletion and Hemodynamic Instability Systematic review and meta-analysis Tea et al (193) NSAID, diuretics and other nephrotoxic drugs Systematic review and meta-analysis Zhang et al (194) ACE-I/ARB usage Randomized trial parallel-group, single-center CAPTAIN trial (195) Acute heart failure NYHA III-IV Multicenter retrospective study Tian et al (196) Hypoalbuminemia Systematic review and meta-analysis Liwei et al (197) Peri-procedural hyperglycemia Systematic review and meta-analysis Jakrin et al (198) Patient…”
Section: Patient-related Risk Factors-modifiable Weight Of Evidence E...mentioning
confidence: 99%
“…It has been reported that both procedure- and patient-related risk factors can impact the initiation and progression of CI-AKI, including the volume of contrast agents, pre-existing kidney failure, diabetes, and hemodynamic instability ( Azzalini et al, 2016 ). Our previous studies also proved that the severity of heart failure and the absence of statin application before admission were both independent predictors for CI-AKI ( Lin et al, 2021 ; Xu et al, 2021 ). Considering that CI-AKI can increase the risk of mortality, it is important to identify risk factors for early detection and prevention of the incidence of CI-AKI ( Legnazzi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 63%
“…The incidence of CI-AKI is reportedly high worldwide and varies from 4.4 to 22.1% according to different definitions (7). Various risk factors, including diabetes, heart failure severity, anemia, renal dysfunction and circulatory insufficiency, have been identified to promote the occurrence of CI-AKI (8)(9)(10). Of the various factors associated with the CI-AKI, inflammation has been demonstrated to be an important risk factor and inflammationbased predictors can effectively determine high-risk CI-AKI (11,12).…”
Section: Introductionmentioning
confidence: 99%